Functional dried noodles with snakehead fish and yellow sweet potato flour to support stunting prevention - Permana Agung; Hijrah Asikin; Thresia Dewi Kartini B; Sirajuddin Sirajuddin; Mustamin Mustamin; Kurnia Taqwa (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Stunting is a chronic nutritional problem caused by a prolonged inadequate intake of nutrients, particularly protein and iron. Its management requires local food innovations that are nutrient-dense, acceptable, and affordable. Dried noodles substituted with snakehead fish flour and yellow sweet potato flour have the potential to increase energy density and essential nutrient content, making them a viable alternative for local supplementary feeding (PMT) in children at risk of stunting. This study aimed to determine the chemical characteristics and organoleptic properties of dried noodles. A pre-experimental design was used, with one control formula and three treatment formulas, conducted at the Food Technology and Organoleptic Laboratory, Poltekkes Kemenkes Makassar, and the Feed Chemistry Laboratory, Hasanuddin University (June 2023–March 2024). The energy, protein, carbohydrate, iron, zinc, and vitamin C contents were analyzed in duplicate, and organoleptic testing was performed by 50 semi-trained panelists. Significant differences were observed in protein, iron, carbohydrate, color, and taste (p<0.05), but not in energy, zinc, vitamin C, or texture (p>0.05). In conclusion, formula F3 was the best, containing 340.30 kcal/100 g energy, 21.92% protein, 65.67 g/100 g carbohydrate, 4.10 mg/100 g iron, 3.17 mg/100 g zinc, and 49.24 mg/100 g vitamin C.